2015
DOI: 10.1113/jp271081
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on cerebral perfusion, oxygenation and metabolism during exercise in humans

Abstract: Igor Braz received his medical degree from the Universidade Federal Fluminense in Rio de Janeiro state, Brazil. He is currently undertaking a PhD in human cerebrovascular control, at the University of Birmingham, UK, under the guidance of Dr James Fisher and Prof. Gregory Lip. In the future, he hopes to combine his passions of clinical practice and physiological research. James Fisher is currently a Senior Lecturer in Exercise Physiology in the School of Sport, Exercise and Rehabilitation Sciences at the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 104 publications
(246 reference statements)
1
24
0
1
Order By: Relevance
“…Although numerous studies have demonstrated an association between lower levels of resting perfusion and poorer cognition, particularly on speed-dependent indices [24], few have examined changes in regional perfusion and cognitive change. Our finding that improved MCA perfusion was associated with increased processing speed is consistent with prior studies demonstrating that exercise-induced MCA perfusion is associated with improved processing speed [25,26]. In addition, poorer perfusion in brain regions supported by MCA subsidiary vasculature has been associated with lower processing speed among individuals with mild Alzheimer's disease [27] and carotid disease [28], suggesting that MCA-perfused structures (eg, posterior cingulate) may be particularly important for information processing efficiency.…”
Section: Commentsupporting
confidence: 88%
“…Although numerous studies have demonstrated an association between lower levels of resting perfusion and poorer cognition, particularly on speed-dependent indices [24], few have examined changes in regional perfusion and cognitive change. Our finding that improved MCA perfusion was associated with increased processing speed is consistent with prior studies demonstrating that exercise-induced MCA perfusion is associated with improved processing speed [25,26]. In addition, poorer perfusion in brain regions supported by MCA subsidiary vasculature has been associated with lower processing speed among individuals with mild Alzheimer's disease [27] and carotid disease [28], suggesting that MCA-perfused structures (eg, posterior cingulate) may be particularly important for information processing efficiency.…”
Section: Commentsupporting
confidence: 88%
“…Neuronal integration involves multiple cognitive functions and neuronal networks, including work memory and spatial memory (Tucker and Stern, 2011 ; Moon et al, 2017 ). Both neurons and astrocytes need a constant supply of nutrients (glucose and lactate) and oxygen, and regional cerebral oxygenation may be limited during exercise (Nielsen et al, 1999 ; Rooks et al, 2010 ; Braz and Fisher, 2016 ) with a change in the balance of cerebraI metabolism (Avola et al, 2004 ; Dalsgaard and Secher, 2007 ; van Hall et al, 2009 ). In addition, specific neurotrophic growth factors seem to be released as a result of moderate physical exercise, which increases the expression of brain-derived neurotrophic factor (BDNF) and neuronal growth factor (NGF) (Tyler and Pozzo-Miller, 2003 ; Dietrich et al, 2008 ; Seifert et al, 2010 ; Bonini et al, 2013 ; Coelho et al, 2014 ; Hashimoto et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It included the mean measures on both occasions for inter-rater reproducibility. Cerebral blood flow often reduces after 50 years of age [ 14 ]; therefore, the average-measures ICCs for each cerebral artery were compared between participants aged less than 50 years and those aged at least 50 years. Likewise, those ICCs were compared between the controls and the patient group.…”
Section: Methodsmentioning
confidence: 99%